Multi-material single-vat dual-wavelength DLP 4D printing of shape memory polymers [data] - Kröger, Finn; Schulte, Lennard; Spiegel, Christoph A.; Vázquez-Martel, Clara; Blasco, Eva (Universität, 2024)
Shape memory polymers (SMP) are a fascinating class of responsive materials with potential in various fields, especially when combined with precise structuring by 3D printing strategies such as digital light processing (DLP). However, such 3D printing techniques are usually limited to homogeneous single material 4D structures restricting potential applicability. In this study we present a dual-wavelength multi-material DLP-based strategy for the fabrication of 4D multi-material structures with a spatial controllable shape memory effect from a single ink formulation. To achieve this, we designed an ink system, allowing generation of static as well as responsive parts depending on the applied curing wavelength with a high spatial control. Specifically, the multi-material ink formulations are composed of epoxide-based, (meth)acrylate-based monomers and a radical photoinitiator - providing appropriate selectivity of the polymerization mechanism. A germanium-based derivative has been selected as a suitable radical photoinitiator active in the blue wavelength regime (460 nm), enabling the exclusive formation of poly(meth)acrylate-based networks exhibiting shape memory properties. When printing with UV light (365 nm), simultaneous formation of epoxy and polymethacrylate networks results in a non-responsive material. Finally, by exploiting these capabilities, the fabrication of multi-material 4D structures with spatially controllable shape memory properties are successfully demonstrated.
Gefördert durch: Deutsche Forschungsgesellschaft (DFG): SFB1249; Carl-Zeiss-Foundation-FocusHEiKA; SDS@hd Datenspeicherdienst
Gesehen am 27.08.2025
Keywords: Forschungsdaten; Datenbank